2007
DOI: 10.1039/b707762a
|View full text |Cite
|
Sign up to set email alerts
|

A cryptic PKS–NRPS gene locus in the plant commensal Pseudomonas fluorescens Pf-5 codes for the biosynthesis of an antimitotic rhizoxin complex

Abstract: Targeted gene inactivation and metabolic profiling revealed that the cryptic PKS-NRPS gene cluster in the genome of the plant commensal Pseudomonas fluorescens Pf-5 codes for the biosynthesis of antiproliferative and antifungal rhizoxin derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 14 publications
1
44
0
1
Order By: Relevance
“…(12) and Pseudomonas sp. (13). Further downstream, the PKS genes have resemblances to gene clusters reported from various Nostocales or Oscillatoriales.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…(12) and Pseudomonas sp. (13). Further downstream, the PKS genes have resemblances to gene clusters reported from various Nostocales or Oscillatoriales.…”
Section: Resultsmentioning
confidence: 88%
“…S6-S9). This method allowed collection of highquality 1 H-and 13 C-spectra, as well as COSY-, HSQC-, and HMBC-2D-NMR data from microgram amounts of the 13 The NMR data fully supported the identity of the compound as a member of the pederin group and allowed elucidation of its constitution. In combination with bioinformatic analysis it was possible to predict most of the stereogenic elements, except the configuration at C12 and C14 ( Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…However, WF-1360 B and the new compound 22Z-WF-1360 F, which were detected in Pf-5 culture supernatants in this study, were not reported previously. Instead, Brendel et al (4) isolated from cultures of Pf-5 several seco-rhizoxins, derivatives with an open ␦-lactone ring. These seco-rhizoxins included rhizoxin D3, S1, S2, and Z1, which are the corresponding seco forms of WF-1360 C, WF-1360B, WF-1360 F, and 22Z-WF-1360 F, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Because few growing chains with both ␣-and ␤-keto groups have been examined on PKS assembly-line modules, it is not yet known how many dual-functioning ␣/␤ KR domains exist. Blastp searches of the dual-function PksJ-KR revealed numerous orthologs predominantly in trans-AT clusters, including those responsible for mupirocin, bryostatin, and rhizoxin biosynthesis (19,20), with 44%, 44%, and 43% sequence identity, respectively. Notably, many of these possible dual-function ␣/␤ KRs are predicted to act on C 2 -extended ␣-ketoacyl-Gly-S-T thioesters, perhaps reflecting a preference for conformationally flexible substrates (21).…”
Section: Discussionmentioning
confidence: 99%